Thesis on oophorectomy - Gall, D. E. (My University, 1908)
Introduction: History. – Ovariectomy is one of the oldest operations in veterinary surgery, it originated about the same time as the same operation in women. Ovariectomy is both described by ancient and modern writers. It is mentioned by Aristotle (4th century B. C.), Varro (1st century B. C.) and Pliny (1st century A. D.).
Citation: Gall, D. E. Thesis on oophorectomy. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Oophorectomy; Anatomy; Ovaries; Veterinarian; Graduating theses; Senior theses; Theses